Porous silver electrode slurry and preparation method thereof
By using high-tap-density silver powder and silver powder with a specific particle size ratio, combined with a dispersion system of isophorone, diacetone alcohol, and polyamide wax, the problems of complex processes and poor performance of existing pore-filling slurries in LTCC product manufacturing have been solved, achieving efficient and environmentally friendly electrode preparation and improving product quality and production efficiency.
Patent Information
- Application Number
- CN202411592768.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing pore-filling slurries have problems such as complex processes, reduced conductivity, and poor bonding performance in the manufacture of LTCC products, which affect product quality.
Using high tap density silver powder as the main component, combined with a specific particle size ratio and the combination of isophorone, diacetone alcohol and polyamide wax, a stable dispersion system is formed, which ensures the uniform distribution and tight arrangement of silver powder in the slurry and simplifies the preparation process.
It improves the fullness and uniformity of the filling effect, enhances the mechanical strength and conductivity of the electrode, simplifies the production process, reduces costs and energy consumption, and meets environmental protection requirements.
Smart Images

Figure CN119296846A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electronic paste, and more specifically, to a hole-filling silver electrode paste and a preparation method thereof. Background Art
[0002] In the field of electronic paste technology, hole-filling electrode silver paste, as a key material, plays a vital role in the manufacture of LTCC (low-temperature co-fired ceramic) electronic components, especially it is widely used in the manufacturing process of through-hole electrodes of LTCC products. LTCC RF electronic components are advanced components that integrate multilayer ceramic technology. This technology embeds and integrates capacitors, inductors and resistors into low-temperature co-fired ceramic substrates to form integrated ceramic components with specific functions. With its miniaturized and highly flexible integrated design, this type of component has shown significant advantages in the development trend of electronic products that are increasingly pursuing miniaturization, digitization, integration and low cost. Especially in dense circuit board layouts, LTCC can save a lot of space. At the same time, its low loss, high out-of-band suppression, wide bandwidth and high reliability have made the output of LTCC products show a rapid growth trend in recent years.
[0003] However, in the manufacturing process of LTCC products, the quality of the connecting electrode, as the key node connecting the product layers, directly determines the overall performance and reliability of the product. Once the connecting electrode has problems, such as virtual connection or open circuit, it will directly threaten the stability and service life of the product. Therefore, the quality of the silver paste for filling the hole of the connecting electrode is particularly important.
[0004] In order to achieve a good hole-filling effect, the hole-filling slurries commonly used in the market often need to be doped with various metal and non-metal materials. This practice not only has complex process technology and significantly reduces the conductivity of the connecting point electrode, but also has poor connection performance between the connecting point and the internal silver electrode, seriously affecting product quality.
[0005] Based on the shortcomings of existing hole filling slurries in the manufacture of LTCC products, it is very necessary to overcome the above defects and improve the performance and quality of LTCC products. Summary of the invention
[0006] In order to solve the above problems, the present application provides a pore-filling silver electrode slurry and a preparation method thereof.
[0007] In a first aspect, the present application provides a pore-filling silver electrode slurry, which adopts the following technical solution: A hole-filling silver electrode slurry comprises the following components by weight percentage: 85%-90% silver powder, an organic carrier, 0.1%-0.5% isophorone, 0.1%-0.5% diacetone alcohol, and 0.1%-1% polyamide wax; Silver powder includes silver micro powder and submicron silver powder, and the ratio of silver micro powder to submicron silver powder is (8-10): 1; The particle size of silver micropowder is 1.5-2.5μm, and the tap density is greater than 6.5g / ml; the particle size of submicron silver powder is 0.3-0.6μm, and the tap density is greater than 5.5g / ml.
[0008] This application abandons the traditional practice of doping metal or non-metallic materials, and adopts high tap density and specific silver powder as the main component of the hole-filling electrode silver paste. This application not only avoids the impurity problem caused by doping, but also makes full use of the excellent filling and dispersibility of the high tap density silver powder itself. High tap density and specifically selected silver powder means that the gaps between particles are smaller and the arrangement is tighter, thus forming a more stable structure in the slurry. This structure can effectively resist shrinkage during the sintering process, making the final hole filling effect fuller, reducing the generation of pores and defects, and reducing the shrinkage of the slurry during the firing process.
[0009] The present application achieves uniformity of particle distribution by limiting the special dosage relationship of the size of silver powder. This uniform distribution not only improves the density of the pore filling, but also makes the electrode more uniform during the formation process, avoiding local defects caused by uneven particle size. In addition, the ratio of large and small particle sizes also helps to form a more compact network structure during the sintering process, further enhancing the mechanical strength and conductivity of the electrode.
[0010] In addition, the present application further utilizes the special combination of isophorone, diacetone alcohol, and polyamide wax. The combination of the three enhances the solubility and volatility of the system, and forms a special and stable dispersion system with the silver powder particles, ensuring the uniform distribution of the silver powder in the slurry. This uniform distribution provides a good foundation for the subsequent sintering process, allowing the silver powder particles to be arranged more closely together during sintering. It also effectively improves the fluidity and plasticity of the slurry, making the slurry easier to fill and shape.
[0011] The volatility of isophorone and diacetone alcohol helps the slurry to quickly discharge the solvent during the sintering process, thereby avoiding the generation of pores and defects. The decomposition and volatilization of polyamide wax can also promote the close arrangement and fusion of silver powder particles, further improving the density of the electrode after sintering.
[0012] Due to the uniform distribution of silver powder particles in the slurry and their close arrangement, the electrode has higher density and conductivity after sintering. This dense structure reduces the generation of pores and defects and improves the fullness and uniformity of the hole filling effect. The close arrangement and fusion of silver powder particles make the electrode have higher conductivity and mechanical strength after sintering. This improvement optimizes the overall performance of electronic components, with lower resistance, higher conductivity efficiency and more stable performance.
[0013] Preferably, in terms of weight percentage, the isophorone is 0.1%-0.3%, the diacetone alcohol is 0.1%-0.3%, and the polyamide wax is 0.5%-1.0%.
[0014] Preferably, the composition comprises the following components in terms of weight percentage: 86% silver powder, 13% organic carrier, 0.2% isophorone, 0.3% diacetone alcohol, and 0.5% polyamide wax.
[0015] By adopting the above technical solution, the special dosage relationship of isophorone, diacetone alcohol and polyamide wax in the system is further defined, which can more fully promote the formation of a stable dispersion system with silver powder. This dispersion system not only helps the uniform distribution of silver powder particles in the slurry, but also prevents the agglomeration and sedimentation of silver powder particles, thereby improving the stability and service life of the slurry. At the same time, it can enhance the fluidity and plasticity of the slurry, making it easier to fill and shape.
[0016] Preferably, the silver micropowder is spherical or nearly spherical in shape.
[0017] Preferably, the tap density of the silver micropowder is 7.38 g / ml, and the tap density of the submicron silver powder is 6.02 g / ml.
[0018] Preferably, the organic carrier includes a polymer resin and an organic solvent.
[0019] Preferably, according to the weight percentage of the organic carrier, the polymer resin is 10%-30%.
[0020] Preferably, the polymer resin is one or more of ethyl cellulose, nitrocellulose, hydroxy cellulose, and rosin, and the organic solvent is one or more of terpineol, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, turpentine, and cyclohexanone.
[0021] By adopting the above technical solution and further optimizing the specific selection and dosage of the organic carrier, the silver powder and other solid particles can be better wetted, so that they are more evenly dispersed in the slurry, avoiding agglomeration and precipitation. It helps to form a more uniform and denser silver film, improve the conductivity and adhesion. It can also give the system a faster volatilization speed and curing speed, effectively reducing the defects such as bubbles and pinholes generated in the slurry during the hole filling process.
[0022] In the second aspect, the present application provides a method for preparing a pore-filling silver electrode slurry, adopting the following technical scheme: a method for preparing a pore-filling silver electrode slurry, comprising the following steps: mixing various raw materials until uniform, grinding to less than 6.0 μm, and obtaining a pore-filling silver electrode slurry.
[0023] By adopting the above technical solution, a simplified process of directly mixing the raw materials is adopted. This process is not only easy to operate, reduces the need for complex steps and equipment, but also greatly reduces production costs. Through direct mixing, enterprises can quickly respond to market demand, improve production efficiency, and produce a large amount of slurry in a short period of time. In addition, the simplified process reduces energy consumption and waste generation, complies with environmental regulations, and promotes sustainable development.
[0024] In summary, this application has the following beneficial effects: 1. This application abandons the conventional practice of doping metal or non-metallic materials, and instead uses a specific silver powder with high tap density as the core component. This change not only effectively avoids the impurity problem that may be introduced during the doping process, but also makes full use of the excellent filling and dispersibility exhibited by the high tap density silver powder.
[0025] 2. The present invention further defines the special matching relationship between the size of silver powder particles and their dosage, achieving the ultimate uniformity of particle distribution. It not only significantly improves the density of the pore filling, but also ensures the high uniformity of the electrode during the formation stage, effectively avoiding the local defect problem that may be caused by uneven particle size. At the same time, the reasonable ratio of particle size also helps to form a denser and tougher network structure during the sintering process, further enhancing the mechanical strength and conductive properties of the electrode.
[0026] 3. This application further introduces a special combination of isophorone, diacetone alcohol and polyamide wax, which significantly enhances the solubility and volatility of the system and constructs a stable and uniform dispersion system with silver powder particles. This dispersion system ensures the uniform distribution of silver powder in the slurry, lays a good foundation for the sintering process, and promotes the close arrangement of silver powder particles. It also optimizes the fluidity and plasticity of the slurry, making it easier to fill and form. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is an electron microscope image of the silver powder of Example 1.
[0028] Figure 2 This is an electron microscope image of the submicron silver powder of Example 1.
[0029] Figure 3 This is a detection diagram of the connection electrodes of the LTCC radio frequency electronic components made with the hole-filling silver electrode paste of Examples 1-3.
[0030] Figure 4 This is a detection diagram of the connection electrodes of the LTCC radio frequency electronic components made with the hole-filling silver electrode paste of Examples 1-4.
[0031] Figure 5 This is a detection diagram of the connection electrodes of the LTCC radio frequency electronic components made with the hole-filling silver electrode paste of Examples 5-8. DETAILED DESCRIPTION
[0032] The present application is further described in detail below with reference to the accompanying drawings and embodiments.
[0033] The raw materials used in the following examples and comparative examples are all commercially available products. Example
[0034] Example 1 A hole-filling silver electrode slurry comprises the following components: silver powder, an organic carrier, isophorone, diacetone alcohol and polyamide wax.
[0035] Silver powder includes silver micro powder and submicron silver powder.
[0036] Reference Figure 1 The silver micropowder has a spherical or nearly spherical shape, a particle size of 1.5-2.5 μm, and a tap density of 7.38 g / ml.
[0037] The particle size of submicron silver powder is 0.3-0.6μm, the tap density is 6.02g / ml, and its morphology is based on Figure 2 .
[0038] The organic vehicle includes a polymer resin and an organic solvent, and the polymer resin and the organic solvent are mixed until uniform to prepare the organic vehicle.
[0039] The polymer resin is ethyl cellulose and the organic solvent is pinene alcohol.
[0040] The specific content of each component is shown in Table 1.
[0041] The present application also provides a method for preparing a pore-filling silver electrode slurry, comprising the following steps: Step 1: Mix the raw materials according to the recipe.
[0042] Step 2: Put all the raw materials into the vacuum mixer and mix until smooth.
[0043] Step 3: Grind the material in step 2 to 5.5 μm using a three-roll mill, filter, adjust, and package to make a pore-filling silver electrode slurry.
[0044] Example 2 A pore-filling silver electrode paste, which is different from Example 1 in that: The tap density of silver micropowder is 6.5g / ml.
[0045] The tap density of submicron silver powder is 5.5 g / ml.
[0046] In the organic carrier, the polymer resin is nitrocellulose and the organic solvent is cyclohexanone.
[0047] The specific content of each component is different, see Table 1 for details.
[0048] Example 3 A pore-filling silver electrode slurry, which is different from Example 1 in that: The tap density of silver micropowder is 8.5g / ml.
[0049] The tap density of submicron silver powder is 7.5 g / ml.
[0050] In the organic carrier, the polymer resin is rosin, and the organic solvent is ethylene glycol ethyl ether acetate.
[0051] The specific content of each component is different, see Table 1 for details.
[0052] Table 1 Comparative Example Comparative Example 1 A pore-filling silver electrode slurry, which is different from Example 1 in that the silver micropowder is 86 kg and the submicron silver powder is 0 kg.
[0053] Comparative Example 2 A pore-filling silver electrode slurry, which is different from Example 1 in that the silver micropowder is 43 kg and the submicron silver powder is 43 kg.
[0054] Comparative Example 3 A hole-filling silver electrode slurry, which is different from Example 1 in that isophorone and diacetone alcohol are replaced by an organic silicon leveling agent, that is, the isophorone and diacetone alcohol are 0 kg, and the organic silicon leveling agent is 0.5 kg.
[0055] The organosilicon leveling agent is commercially available from Dongguan Sinobo New Material Technology Co., Ltd., model number S401.
[0056] Comparative Example 4 A hole-filling silver electrode slurry, which is different from Example 1 in that isophorone is replaced by diacetone alcohol, that is, the isophorone is 0 kg and the diacetone alcohol is 0.5 kg.
[0057] Comparative Example 5 A hole-filling silver electrode slurry, which is different from Example 1 in that diacetone alcohol is replaced by isophorone, that is, the isophorone is 0.5 kg and the diacetone alcohol is 0 kg.
[0058] Comparative Example 6 A pore-filling silver electrode slurry, which is different from Example 1 in that the polyamide wax is replaced by hydrogenated castor oil, that is, the polyamide wax is 0 kg and the hydrogenated castor oil is 0.5 kg.
[0059] Comparative Example 7 A pore-filling silver electrode slurry, which is different from Example 1 in that: The tap density of silver micropowder is 5.6g / ml.
[0060] The tap density of submicron silver powder is 1g / ml.
[0061] Comparative Example 8 A pore-filling silver electrode slurry, which is different from Example 1 in that the silver micropowder is 85 kg, the submicron silver powder is 0 kg, and the glass powder is 1 kg.
[0062] Performance testing The hole-filling silver electrode paste is used to prepare LTCC radio frequency electronic components according to the common preparation method of those skilled in the art (the hole-filling silver electrode paste in Examples 1-3 and Comparative Examples 1-8 is printed into hole-filling connection point electrodes using a screen printing process, and then sintered. The sintering conditions include: sintering in a tunnel furnace under atmospheric atmosphere, a peak temperature of 850-920°C, and a peak time of 1-2.5 hours), and the connection electrode detection results are observed.
[0063] If both ends of the connected electrode diagram are filled and there are no black holes, it is qualified, otherwise it is unqualified.
[0064] The test results are summarized in Table 2. For specific test diagrams, refer to Figure 3-5 .
[0065] Table 2 Group Electrode appearance grinding test results Example 1 The electrode appearance is qualified Example 2 The electrode appearance is qualified Example 3 The electrode appearance is qualified Comparative Example 1 The electrode is cracked inside and is unqualified. Comparative Example 2 Internal cracks and side cracks in the electrode, unqualified Comparative Example 3 Internal cracks and lack of silver in the electrode, unqualified Comparative Example 4 The electrode lacks silver and is unqualified Comparative Example 5 Electrode side crack, unqualified Comparative Example 6 The magnet on the side of the electrode is slightly cracked, unqualified Comparative Example 7 The upper and lower ends of the electrode are cracked, which is unqualified Comparative Example 8 The upper and lower ends and sides of the electrode are cracked, which is unqualified. According to Table 2, the LTCC RF electronic components made of the hole-filling silver electrode pastes of Examples 1-3 are qualified products because both ends of the connected electrode diagram are filled in during the connection electrode detection, and there are no black holes. The technical solution provided by this application does not require doping with various metals or non-metallic materials, and the process technology is simple. The conductivity of the connection point electrode can be effectively improved, and the connection performance between the connection point and the internal silver electrode is good, which significantly improves the product quality.
[0066] The pore-filling silver electrode pastes of Comparative Examples 1-7 are based on Example 1, but the special selection of silver powder or the special matching relationship of isophorone, diacetone alcohol and polyamide wax is destroyed; Comparative Example 8 simulates the pore-filling silver electrode paste made by adding inorganic additives on the market. According to Table 2 and the attached drawings, the products of Comparative Examples 1-8 are all unqualified.
[0067] It is explained that the application further limits the use of silver micropowder and submicron silver powder, which can effectively achieve the particle size grade matching of silver powder, improve the uniformity of the slurry during the firing shrinkage process, and avoid the local defects of electrode internal cracks caused by uneven shrinkage of silver powder during the firing process.
[0068] At the same time, the special combination of isophorone, diacetone alcohol and polyamide wax can ensure the uniform distribution of silver powder in the slurry, enhance the fluidity and plasticity of the slurry, and make the slurry easier to fill and shape. This provides a good foundation for the subsequent sintering process, allowing the silver powder particles to be arranged more closely during sintering and improve performance.
[0069] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A pore-filling silver electrode slurry, characterized in that: According to weight percentage, it includes the following components: 85%-90% silver powder, organic carrier, 0.1%-0.5% isophorone, 0.1%-0.5% diacetone alcohol, and 0.1%-1% polyamide wax; Silver powder includes silver micro powder and submicron silver powder. Silver micro powder: submicron silver powder is (8-10): 1; The particle size of silver micropowder is 1.5-2.5μm, and the tap density is greater than 6.5g / ml; the particle size of submicron silver powder is 0.3-0.6μm, and the tap density is greater than 5.5g / ml.
2. The pore-filling silver electrode slurry according to claim 1, characterized in that: According to weight percentage, the isophorone is 0.1%-0.3%, the diacetone alcohol is 0.1%-0.3%, and the polyamide wax is 0.5%-1.0%.
3. The pore-filling silver electrode slurry according to claim 1, characterized in that: According to weight percentage, the composition includes: 86% silver powder, 13% organic carrier, 0.2% isophorone, 0.3% diacetone alcohol, and 0.5% polyamide wax.
4. The pore-filling silver electrode slurry according to claim 1, characterized in that: The silver micropowder is spherical or nearly spherical in shape.
5. The pore-filling silver electrode slurry according to claim 1, characterized in that: The tap density of the silver micropowder is 7.38 g / ml, and the tap density of the submicron silver powder is 6.02 g / ml.
6. The pore-filling silver electrode slurry according to claim 1, characterized in that: The organic carrier includes a polymer resin and an organic solvent.
7. The pore-filling silver electrode slurry according to claim 6, characterized in that: According to the weight percentage of the organic carrier, the polymer resin is 10%-30%.
8. The pore-filling silver electrode slurry according to claim 7, characterized in that: The polymer resin is one or more of ethyl cellulose, nitrocellulose, hydroxy cellulose and rosin, and the organic solvent is one or more of terpineol, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, turpentine and cyclohexanone.
9. A method for preparing the pore-filling silver electrode slurry according to any one of claims 1 to 8, characterized in that: The following steps are involved: Various raw materials are mixed until uniform, and ground to less than 6.0 μm to obtain a pore-filling silver electrode slurry.
Citation Information
Patent Citations
Solar battery back silver paste and preparing method thereof as well as solar battery and preparing method thereof
CN104681123A
Back electrode silver paste composition and preparation method thereof, and solar cell
CN114530277A
Electrode slurry, preparation method and photovoltaic cell
CN114898911A
Method for preparing low-temperature silver paste for HJT battery by using high-tap-density micron silver powder
CN115620958A
Low-temperature curing type conductive silver paste, preparation method and application thereof
CN117976288A